Trichoderma atroviride enhances phenolic synthesis and cucumber protection against Rhizoctonia solani - Justyna Nawrocka; Magdalena Szczech; Urszula Małolepsza (Plant Protection Science, 2018)
The treatment of cucumber plants with Trichoderma atroviride TRS25 (TRS25) provided protection against infection by Rhizoctonia solani. In plants inoculated with the pathogen, nontreated with Trichoderma, disease symptoms were observed on the roots, shoots, and leaves while in plants treated with TRS25 the spread of the disease was limited. The induction of systemic defence response in cucumber against R. solani infection seemed to be strongly related to the enhanced synthesis of phenolic compounds in plants. HPLC analysis indicated remarkable increases in the concentrations of 23 phenolics belonging to hydroxybenzoic acids, cinnamic acids, catechins, flavonols, flavons, and flavanons in the plants without systemic disease symptoms. We suggest that the accumulation of phenolic acids, flavonoids and de novo synthesis of catechins may strongly contribute to cucumber protection against R. solani.